Analisis Kualitas Website Editornews.Id dengan Metode Webqual 4.0 - Nita Christine; Benni Purnama; Herry Mulyono (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2024)
Editornews.id is one of the online news sites in Jambi City, which has several problems that are often felt by users, such as excessive advertising, news that is not timely and there is no column for direct interaction on the website. From these problems, researchers are interested in researching the Editornews.id website. To analyze website quality and the influence of each variable on user satisfaction. This study uses the WebQual 4.0 method to know website quality, website performance, and user expectations using Usability, Information Quality, Service Interaction Quality, and User Satisfaction variables with a sample size of 230 respondents. Data analysis is processed with SPSS software. The results based on the results of the analysis show that the Usability variable (X1) affects User Satisfaction, the Information Quality variable (X2) has no effect on User Satisfaction, the Service Interaction Service variable (X3) affects User Satisfaction and the Usability variable (X1), Information Quality (X2), Service Interaction Quality (X3) together affect User Satisfaction. So Editornews.id must improve the reputation and appearance of the website and improve the information delivery system on the website.